See you at the top - Ziglar, Zig, ....-; Mayton, Al, ....- (Gretna : Pelican, 2005)
The 25th anniversary edition of the classic motivational and self-improvement book that has sold more than 1.6 million copies in hardcover. For more than three decades, Zig Ziglar, one of the great motivators of our age, has traveled the world, encouraging, uplifting, and inspiring audiences. His groundbreaking best-seller, See You at the Top, remains an authentic American classic. This revised and updated edition stresses the importance of honesty, loyalty, faith, integrity, and strong personal character.
Originally published: as Biscuits, fleas and pump handles. 1977.
Keywords: Conduct of life; Self-actualization (Psychology).; Success